Exploring the Impact of the Publicness of Public Space in Hong Kong: A Structural Equation Modelling Approach - He-Ming Zeng; Louie Sieh; Dong Zhang; Hao Huang; Yu-Zun Zhang; Jin-Yeu Tsou (Land)
Public spaces are spaces that are open to the public, and their publicness denotes the degree to which the space is inclusive, accessible, and representative of collective interests, fostering diverse activities, and ultimately enhancing social cohesion and urban vitality. While existing studies have focused on interpreting and assessing the concept of publicness, few explore its specific impact within public spaces. This study aims to identify the impact of the publicness of public space and develop an assessment model. Based on a literature review, five publicness impacts are proposed: effectiveness, fairness, sense of ease, meaningfulness, and friendliness. Two rounds of questionnaire surveys were conducted on public space users in Hong Kong, with a total of 305 responses received. The collected data were used to test and validate the model through exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM). The developed model offers a robust tool for determining whether a space is public. The findings show correlations among the five impacts of publicness, except between fairness and meaningfulness, which may imply that, in the Hong Kong public space, fairness is a functional or procedural requirement rather than a deep emotional or spiritual connection with the space.